Engineering a Tumor Microenvironment‐Mimetic Niche for Tissue Regeneration with Xenogeneic Cancer Cells. Issue 3 (2nd January 2018) - Wang, Zhenzhen; Wang, Chunming; Abudukeremu, Ayipaxia; Rui, Xiaying; Liu, Shang; Zhang, Xiaoyi; Zhang, Min; Zhang, Junfeng; Dong, Lei
Abstract: The insufficient number of cells suitable for transplantation is a long‐standing problem to cell‐based therapies aimed at tissue regeneration. Xenogeneic cancer cells (XCC) may be an alternative source of therapeutic cells, but their transplantation risks both immune rejection and unwanted spreading. In this study, a strategy to facilitate XCC transplantation is reported and their spreading in vivo is confined by constructing an engineering matrix that mimics the characteristics of tumor microenvironment. The data show that this matrix, a tumor homogenate‐containing hydrogel (THAG), successfully creates an immunosuppressive enclave after transplantation into immunocompetent mice. XCC of different species and tissue origins seeded into THAG survive well, integrated with the host and developed the intrinsic morphology of the native tissue, without being eliminated or spreading out of the enclave. Most strikingly, immortalized human hepatocyte cells and rat β‐cells loaded into THAG exert the physiological functions of the human liver and rat pancreas islets, respectively, in the mouse body. This study demonstrates a novel and feasible approach to harness the unique features of tumor development for tissue transplantation and regenerative medicine. Abstract : An engineered tumor microenvironment mimetic niche formed by active soluble factors in tumor extract (tumor homogenate), basic fibroblast growth factor, and injectable hydrogel facilitates the xenogeneic cancer cells to develop into a functional tissue in immunocompetent mice and confines their unwanted spreading in vivo.